A Branch and Bound Algorithm for the Critical Grid Coverage Problem in Wireless Sensor Networks - Maher Rebai; Matthieu Le Berre; Faicel Hnaien; Hichem Snoussi; Lyes Khoukhi (International Journal of Distributed Sensor Networks)
We aim to cover a grid fully by deploying the necessary wireless sensors while maintaining connectivity between the deployed sensors and a base station ( the sink ). The problem is NP - Complete as it can be reduced to a 2 - dimensional critical coverage problem, which is an NP - Complete problem. We develop a branch and bound (B&B) algorithm to solve the problem optimally. We verify by computational experiments that the proposed B&B algorithm is more efficient, in terms of computation time, than the integer linear programming model developed by Rebai et al. (2013), for the same problem.